Impact of sensory organization tasks on prefrontal cortex activity in older women: a comparative fNIRS study of osteoarthritis and healthy aging - Bishnoi, Alka; Hu, Yang; Hernandez, Manuel E. (Frontiers in Aging Neuroscience, 2025)
IntroductionOsteoarthritis (OA), a prevalent musculoskeletal condition, is associated with an increased risk of falls. Maintaining posture relies on visual, vestibular, and proprioceptive inputs, but these systems can be compromised due to aging or disease, heightening fall risk. Such impairments may result from neuromuscular decline and reduced cognitive or visuospatial processing abilities. This study aimed to investigate prefrontal cortical (PFC) activation patterns during clinical sensory organization tasks (SOT) using functional near-infrared spectroscopy (fNIRS) in older women with OA and healthy controls (HOA). We hypothesized that PFC activation would increase as SOT conditions became more challenging, but that increases would be limited in OA, relative to HOA, given a decreased attentional capacity due to chronic pain.MethodsA cross-sectional study was conducted with 10 women with OA (65.7 ± 3.01 years) and 11 HOA (66.0 ± 4.86 years). Baseline cognitive and motor assessments preceded three trials of six SOT conditions.ResultsSignificant differences between groups in BMI, WOMAC pain score, repeated chair stand, and TUG scores were found (p < 0.001). Linear mixed-model analysis revealed significant effects of condition (CND; p < 0.001), trial (TR; p < 0.0001), and interactions between CND*TR (p < 0.01) and Cohort*CND (p < 0.01) on PFC activation.DiscussionIn conclusion, both groups demonstrated increased PFC activation with task difficulty. However, OA participants exhibited diminished capacity to recruit additional attentional resources compared to HOA, emphasizing the need for further research with larger cohorts to elucidate these findings.